Comparative effectiveness analysis of social media monitoring tools - Duffková, Pavlína (2012)
The main objective of this master thesis is a comparative effectiveness analysis of selected social media monitoring tools. The theoretical part of the thesis first familiarizes the reader with the core terms, which will be used throughout the thesis. The next chapter focuses on the detailed specification of classic online marketing. It describes the growing trend of social media marketing and charts out its current status on the Czech online market. In addition, the vital SEO and SEM techniques are also described. The subsequent chapter is devoted to social network marketing, where the increasing power of "word of mouth" in purchase behavior, is explained. Last but not least, illustrative examples of the most successful social media marketing campaigns are listed. The next part deals with the issues of monitoring social media. The reasons for monitoring social media, its principles and features are stated in this chapter. The practical part of this thesis has a described methodology for testing selected tools, acceptance criteria and metrics of measurement. The selected tools are compared in terms of qualitative properties and the relevance of results, both from a global perspective with English phrases, as well as from the perspective of local phrases suitable for the Czech environment. In the second test a set of free monitoring tools is determined and compared with the tools from the first test. In the conclusion is the last measurement, which is proposes the most appropriate monitoring tool for small sized Czech company.